2020
DOI: 10.3389/fpsyg.2020.00547
|View full text |Cite
|
Sign up to set email alerts
|

Spelling Performance of Portuguese Children: Comparison Between Grade Level, Misspelling Type, and Assessment Task

Abstract: There is consensus among researchers that misspellings are something to avoid. However, misspellings also convey relevant information for researchers and educators. The present study is a first effort toward the analysis of misspellings produced by Portuguese children. Specifically, we aimed to examine the association between misspellings in dictation and composing tasks; compare misspellings across grade, type, and task; and test the contribution of different misspellings produced in dictation and in composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
4
14
0
1
Order By: Relevance
“…This is in line with previous research (Bahr et al, 2012) and suggests that sound-based spellings are learned in the earliest phases of spelling development (Treiman and Bourassa, 2000). Third, stress mark errors were the most frequent misspelling in both timepoints and cohorts, also corroborating past findings with younger Portuguese students (Magalhães et al, 2020). Stress mark errors indicate poor lexical knowledge of stress and difficulties in prosodic and orthographic mapping (Defior et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with previous research (Bahr et al, 2012) and suggests that sound-based spellings are learned in the earliest phases of spelling development (Treiman and Bourassa, 2000). Third, stress mark errors were the most frequent misspelling in both timepoints and cohorts, also corroborating past findings with younger Portuguese students (Magalhães et al, 2020). Stress mark errors indicate poor lexical knowledge of stress and difficulties in prosodic and orthographic mapping (Defior et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Findings from POMAS revealed that from Grades 1 to 9 there was a decrease in phonological errors coupled with an increase in morphological ones, with most errors across grades being orthographic (Bahr et al, 2012). Despite not assessing morphological errors, Magalhães et al (2020) found a similar pattern in Portuguese children from Grades 2, 4, and 6. The authors also found that stress marks errors-largely underexplored in Portuguese studies-were present equally in the assessed grades.…”
Section: Introductionmentioning
confidence: 86%
“…We measured transcription abilities through student's handwriting fluency skills in an alphabet task (Limpo and Alves, 2018), and spelling skills through a dictation task (Magalhães et al, 2020). To measure students' written composition skills, we asked two trained judges to rate the quality of their opinion essays, using a holistic scale ranging from 1 (low quality) to 7 (high quality) (based on Limpo and Alves, 2018).…”
Section: Distal Outcomes -Writing Tasksmentioning
confidence: 99%
“…The mindfulness-related improvements on attention and EFs are expected to generalize to academic achievement (Maynard et al, 2017). Past research already showed that these cognitive skills are related to teacher-rated literacy grades (Magalhães et al, 2020) as well as to specific, writing-related indicators of literacy abilities (Cordeiro et al, 2019). In primary grades, two of these indicators are transcription, which is the externalization of language into written text through the basic processes of handwriting and spelling; and written composition, that is, the production of texts with good and coherently organized ideas, conveyed in well drafted sentences with rich vocabulary.…”
Section: Introductionmentioning
confidence: 98%
“…Sjølve grunntanken om å sjå etter empiriske samanhengar mellom ord og ordval og i vårt tilfelle avvik, kjenner vi også frå forsking innan liknande fenomen som bruken av konservative/radikale former i nynorsk (Helset, 2016), og som nemnt er han nokon gonger utgangspunktet for val av kategoriar (Finbak, 2004(Finbak, , 2005. Magalhães et al (2020) har undersøkt avvik hjå portugisiske barn og mellom anna sett på om avvika er ulike i ulike klassesteg. Samanlikningane er på kategorinivå, dei byggjer altså på ideen om at det er samanheng mellom avvik som fell i same kategori.…”
Section: Problemstillingunclassified